2015
DOI: 10.1016/j.thromres.2015.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Venous Thromboembolism Recurrence, Adjusted for Treatments and Interim Exposures: A Population-based Case-cohort Study

Abstract: Background Predictors of venous thromboembolism (VTE) recurrence are uncertain. Objective To identify predictors of VTE recurrence, adjusted for treatments and interim exposures. Materials and Methods Using Rochester Epidemiology Project resources, all Olmsted County, MN residents with objectively-diagnosed incident VTE over the 13-year period, 1988–2000, who survived ≥1 day were followed for first objectively-diagnosed VTE recurrence. For all patients with recurrence, and a random sample of all surviving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 38 publications
6
41
0
6
Order By: Relevance
“…In agreement with previous studies [25,26], the 5-year cumulative risk of recurrence was highest among cancer patients. The mortality rate is high among cancer patients, and, in the presence of competing risk of death, the cumulative incidence of recurrence is dependent on both the risk of recurrence and the risk of dying [23,24,31].…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with previous studies [25,26], the 5-year cumulative risk of recurrence was highest among cancer patients. The mortality rate is high among cancer patients, and, in the presence of competing risk of death, the cumulative incidence of recurrence is dependent on both the risk of recurrence and the risk of dying [23,24,31].…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, they interact with all parts of the hemostatic system. We also used age and sex as matching parameters although there was no correlation in univariate analysis, because advanced age ([60 years) has been shown as an independent risk factor of venous thromboembolism in previous studies [11,12], and some reports suggest that sex hormones affect thrombosis [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…[47, 48] For this study, we included all Olmsted County residents who consented to access of their medical records for research purposes and had a first lifetime symptomatic leg DVT or PE during the 28-year period, 1973-2000, and active cancer in the three months prior to or after the VTE diagnosis as previously defined. [28, 49] Briefly, a cancer was considered as active if any evidence of cancer (i.e., diagnosis, treatment, progression, oncologist review) was found via medical record review within 92 days prior to the VTE event/index date. At a minimum, any newly diagnosed cancer was considered as active for 6 months from the diagnosis date if not treated by curative surgery.…”
Section: Methodsmentioning
confidence: 99%